Bioinspired spike-like double yolk–shell structured TiO2@ZnIn2S4 for efficient photocatalytic CO2 reduction. Issue 4 (14th January 2022) - She, Ping; Guan, Buyuan; Sheng, Jiyao; Qi, Yuanyuan; Qiao, Guanyu; Rui, Hongbang; Lu, Geyu; Qin, Jun-Sheng; Rao, Heng
Abstract : A spike-like double yolk–shell structured TiO2 @ZnIn2 S4 (D-Y-TiO2 @ZnIn2 S4 ) photocatalyst was designed, which possesses superior photocatalytic CO2 reduction efficiency. Abstract : Photocatalytic carbon dioxide (CO2 ) reduction (PCR) into syngas is one of the sustainable approaches for recycling CO2 into value-added chemical feedstocks. However, the PCR efficiency is often limited by the insufficient light-harvesting and poor charge separation. Herein, we design a spike-like double yolk–shell structured TiO2 @ZnIn2 S4 (D-Y-TiO2 @ZnIn2 S4 ) photocatalyst with superior PCR efficiency. The unique design not only integrates advantages of increasing active sites, surface areas and light-harvesting capacity induced by the hierarchical morphology, but also facilitates photo-induced charge separation based on the heterojunction of TiO2 and ZnIn2 S4 . Owing to the combination of structural and compositional merits, the optimized D-Y-TiO2 @ZnIn2 S4 photocatalyst shows superior PCR performance (325.29 μmol CO per g; 227.18 μmol H2 per g) under visible light. In addition, the ratio of CO/H2 can be tuned from 0.03 to 1.43 by changing the sacrificial hole capture condition. This work provides a prospective way to obtain efficient PCR photocatalysts.